1997
DOI: 10.1021/es960670y
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Recovery of Bacteriophage PRD1 in a Sand and Gravel Aquifer:  Effect of Sewage-Derived Organic Matter

Abstract: To test the effects of sewage-derived organic matter on virus attachment, 32P-labeled bacteriophage PRD1, linear alkylbenzene sulfonates (LAS), and tracers were injected into sewage-contaminated (suboxic, elevated organic matter) and uncontaminated (oxic, low organic matter) zones of an iron oxide-coated quartz sand and gravel aquifer on Cape Cod, MA. In the uncontaminated zone, 83% of the PRD1 were attenuated over the first meter of transport by attachment to aquifer grains. In the contaminated zone, 42% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
136
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(151 citation statements)
references
References 68 publications
12
136
3
Order By: Relevance
“…Under those conditions, detachment can be considered negligible. This is consistent with previous studies, which concluded that the attachment of microbes to soil particles is an irreversible process [24,[54][55][56].…”
Section: Discussionsupporting
confidence: 93%
“…Under those conditions, detachment can be considered negligible. This is consistent with previous studies, which concluded that the attachment of microbes to soil particles is an irreversible process [24,[54][55][56].…”
Section: Discussionsupporting
confidence: 93%
“…Among these particles some are by themselves environmental contaminants (Kessler and Hunt ;Buddemeier and Hunt 1988) while some serve as vehicles to facilitate the transport of a variety of other contaminants that otherwise would be relatively immobile without the presence of the colloids (McCarthy and Zachara 1989;Corapcioglu and Jiang 1993;Grolimund, Borkovec et al 1996;Ryan and Elimelech 1996). Different types of environmentally relevant particles have been studied, including various minerals, Rajagopalan and Chu 1982;Puls and Powell 1992;Ryde, Kihira et al 1992) bacteria and viruses, (Logan, Hilbert et al 1993;Pieper, Ryan et al 1997;Ryan, Elimelech et al 1999;Redman, Walker et al 2004;Walker, Hill et al 2005) and engineered nanoparticles (Lecoanet, Bottero et al 2004;Brant, Lecoanet et al 2005;Saleh, Phenrat et al 2005;Chen and Elimelech 2006;Espinasse, Hotze et al 2007;Jaisi, Saleh et al 2008). The transport and mobility of engineered nanoparticles have been of particular interest over the past few years due to concerns over possible environmental and health impact of these materials (Hoet, Nemmar et al 1999;Colvin 2003;Borm, Robbins et al 2006;Renn and Roco 2006;Wiesner, Lowry et al 2006).…”
Section: Overview Of Deposition Studymentioning
confidence: 99%
“…McCarthy and McKay [18] and Sen et al [122] mentioned in their article that there is a substantial body of published research on microbial transport in the subsurface, much of it focuses on transport in the saturated zone [119][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134]. Transport of bacteria in porous media is mainly bounded with small scale batch and column studies.…”
Section: Biocolloids Transportmentioning
confidence: 99%